2008
DOI: 10.1159/000159276
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of N-Terminal Prohormone Brain Natriuretic Peptides in African Americans with Hypertensive Chronic Kidney Disease: The African American Study of Kidney Disease and Hypertension

Abstract: Background/Aims: The N-amino-terminal fragment of the prohormone B-type natriuretic peptide (NT-proBNP) is a marker of cardiac stress and elevated levels are indicative of heart failure. Few correlates of NT-proBNP levels have been identified in persons with moderate chronic kidney disease (CKD), and data from those without heart failure and from African Americans are especially limited. Methods: The African American Study of Kidney Disease and Hypertension (AASK) enrolled nondiabetic African Americans with hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
1
6
0
2
Order By: Relevance
“…There has been reluctance to adopt the use of NT-proBNP as a biomarker for HF in the CKD population because of the concern that elevated levels might simply be a reflection of reduced clearance from diminished GFR. 8,27 However, similar to our findings, several studies have shown that NT-proBNP levels are strongly associated with cardiovascular events, independent of eGFR levels, in patients with CKD. [28][29][30] In the African-American Study of Kidney Disease and Hypertension, a study of hypertensive black patients with CKD, for each doubling of NT-proBNP, there was a 70% increased risk of HF.…”
Section: Discussionsupporting
confidence: 90%
“…There has been reluctance to adopt the use of NT-proBNP as a biomarker for HF in the CKD population because of the concern that elevated levels might simply be a reflection of reduced clearance from diminished GFR. 8,27 However, similar to our findings, several studies have shown that NT-proBNP levels are strongly associated with cardiovascular events, independent of eGFR levels, in patients with CKD. [28][29][30] In the African-American Study of Kidney Disease and Hypertension, a study of hypertensive black patients with CKD, for each doubling of NT-proBNP, there was a 70% increased risk of HF.…”
Section: Discussionsupporting
confidence: 90%
“…NT-pro-BNP is more stable, with a longer half-life, and may be a better biomarker for chronic volume expansion or stress than is BNP (23). Reduced renal function decreases the fractional plasma clearance of both BNP and NT-pro-BNP, and studies reported correlations between graded elevations in these peptides and declining eGFR or advancing CKD stages (Table 2) (22,(24)(25)(26)(27)(28)(29)(30)(31)(32). The clearance of NT-pro-BNP is predominantly renal, while BNP is also degraded systemically ( Figure 2) (23).…”
Section: Bnp and Nt-pro-bnp In Ckdmentioning
confidence: 99%
“…BNP levels have also been correlated positively with MA cross-sectionally in some clinical reports. 31 There are multiple potential mechanisms whereby aldosterone may lead to altered kidney function, including inflammation and fibrosis. 32 Rats with hypertension that drank saline-infused water had reduced albuminuria on treatment with spironolactone.…”
Section: Potential Mechanismsmentioning
confidence: 99%